(3PcQ eYGfi GdBjGJ GdeJTGHgGJ Edi eYGfi GdBjGJs - (3eMeO Hf CMeO Hf YHO GdeDef GdESYQOj GdOeTbj, TeS GdOjf GHf GddHGf,J (B749 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf CeG HYO MeO Gddg GdhGMO HPGJg hUaGJg aEfc SCdJfi CQTO Hi Gddg hEjGc Yf CeQ YXe ai gPG GdReGf NWg s
(3BNQgG (B:s
(3hPdc jfGai chf GdQH aGYdkG ddbGA , hEPG NQLJg Ydi GdeYfi GdPi PcQfGg de jHb ajg CTcGd hGddg SHMGfg GYde aLQ GdcJGQ s
(3HChdg JedcGJs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B327 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B286s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI YGQa MceJ HGdeOjfI GdefhQI(B((3JaSjQ (B163) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs